1985
DOI: 10.1523/jneurosci.05-05-01222.1985
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged glucocorticoid exposure reduces hippocampal neuron number: implications for aging

Abstract: The hippocampus of the rat loses neurons with age, a loss which may eventuate in some of the functional impairments typical of senescence. Cumulative exposure to corticosterone (CORT) over the lifespan may be a cause of this neuronal loss, as it is prevented by adrenalectomy at mid-age. In this study, we demonstrate that prolonged exposure to CORT accelerates the process of cell loss. Rats were injected daily with sufficient CORT to produce prolonged elevations of circulating titers within the high physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
431
5
16

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,063 publications
(473 citation statements)
references
References 21 publications
(19 reference statements)
21
431
5
16
Order By: Relevance
“…Therefore, stress may perturb gene expression transiently, perhaps via epigenetic effects [97,143], but the withdrawal of the inciting stimulus leads to re-instatement of the original, fully programmed 'steady state.' In addition, whereas neuronal loss has been suspected to occur upon chronic stress in the adult [125,90], most current evidence supports the notion that the structural effects of chronic stress on hippocampal neurons involve dendritic modifications, without cell loss or profound dendritotoxicity. Thus, upon withdrawal of the molecular processes initiated by stress, recovery of both function and structure occurs in mature hippocampus [109,56,114].…”
Section: Recognized Effects Of Stress On Hippocampal Integrity and Fumentioning
confidence: 54%
See 2 more Smart Citations
“…Therefore, stress may perturb gene expression transiently, perhaps via epigenetic effects [97,143], but the withdrawal of the inciting stimulus leads to re-instatement of the original, fully programmed 'steady state.' In addition, whereas neuronal loss has been suspected to occur upon chronic stress in the adult [125,90], most current evidence supports the notion that the structural effects of chronic stress on hippocampal neurons involve dendritic modifications, without cell loss or profound dendritotoxicity. Thus, upon withdrawal of the molecular processes initiated by stress, recovery of both function and structure occurs in mature hippocampus [109,56,114].…”
Section: Recognized Effects Of Stress On Hippocampal Integrity and Fumentioning
confidence: 54%
“…Indeed, LTP was impaired in both CA3 and CA1 hippocampal areas of 12-month old rats stressed early in life [31]. In area CA3, the hippocampal field considered most vulnerable to chronic stress in adults [125,100], both LTP as well as basic synaptic physiology were abnormal [31]. Interestingly, abnormal LTP, although normal synaptic physiology, was found in area CA1 [31].…”
Section: Disruption Of Ltp Induction Accompanies the Profound Memory mentioning
confidence: 99%
See 1 more Smart Citation
“…These results can be interpreted according to the two most prevalent hypotheses, the toxic stress, and the dementia prodrome. According to the toxic-stress hypothesis of depression, high levels of glucocorticoids (McEwen, 1997;Sapolsky, 1993) induce shrinking of the highly sensitive hippocampal gray matter (Sapolsky et al, 1985;Sheline et al, 1999;Steffens et al, 2000;Videbech and Ravnkilde, 2004). According to the prodromal dementia hypothesis of LLD, a subgroup of subjects develops LLD as a very early clinical presentation of dementia (Alexopoulos et al, 1993;O'Brien et al, 2004;Steffens et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found evidence of neuronal atrophy and loss of hippocampal neurons in response to stress (Magarinos et al 1996;Uno et al 1989;Sapolsky et al 1985), and a report of reduced hippocampal volumes in elderly patients with histories of depression suggests that analogous processes may occur in individuals with depression (Sheline et al 1996). Some models of mood disorders (Hyman and Nestler 1996; Post 1992) have attempted to incorporate the notion of compensatory processes into an understanding of the pathophysiologic changes that occur in patients with mood disorders, but few studies have tested these notions empirically (Post 1992).…”
Section: Regulation Of Er Stress Proteins Such As the 78-kilodalton mentioning
confidence: 99%